Perancangan UI/UX Mobile Sistem Informasi Manajemen KKL dan KKN Menggunakan Metode UCD - Muhammad Fauzan Arkan; Muhammad Encep; Himmatul Miftah (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The administrative process for Field Work Practice (KKL) and Community Service (KKN) at theFaculty of Computer Science, Djuanda University, is currently conventional, utilizingdecentralized social media, which triggers coordination inefficiency and data redundancy risks.This study aims to design the interface of the SIMKOM mobile application as an interactive digitalsolution for students in managing KKL and KKN administrative stages. The method employed isUser-Centered Design (UCD) to ensure the design aligns with the users' mental model. Designevaluation was conducted through Heuristic Evaluation with an expert evaluator possessing 5 yearsof experience and Usability Testing with end-users. The research results indicate that designiterations based on Nielsen's 10 Heuristic principles successfully optimized visual consistency,minimalist aesthetics, and information hierarchy. Final testing with 10 student respondentsachieved a 100% task success rate, confirming that the SIMKOM mobile application design isintuitive, effective, and feasible for implementation within the faculty's digital ecosystem.